2022
DOI: 10.1002/kjm2.12506
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine inhibits the growth and metastasis of esophageal cancer cells by down‐regulation of lncRNA MALAT1

Abstract: This study aims to evaluate the effect of dexmedetomidine (DEX)—on esophageal cancer (EC) via regulating long noncoding RNA (lncRNA) metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1). The effect of DEX on MALAT1 expression and EC cell viability was detected. EC cells were divided into Blank, DEX, scrambled/MALAT1 siRNA, and DEX + control/MALAT1 groups, followed by a series of experiments including quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR), western blotting, 3‐[4,5‐dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For instance, it has been reported that one lncRNA, Nuclear paraspeckle assembly transcript 1 (NEAT1), is elevated in EC and modulates miR-377/ E2F3 signaling pathway to encourage EC cell growth and invasion. By controlling the expression of genes involved in cell motility and invasion, a different lncRNA known as metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been related to the metastasis of EC (29,30).…”
Section: The Role Of Lncrnas In Ec Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been reported that one lncRNA, Nuclear paraspeckle assembly transcript 1 (NEAT1), is elevated in EC and modulates miR-377/ E2F3 signaling pathway to encourage EC cell growth and invasion. By controlling the expression of genes involved in cell motility and invasion, a different lncRNA known as metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been related to the metastasis of EC (29,30).…”
Section: The Role Of Lncrnas In Ec Pathogenesismentioning
confidence: 99%
“…Further investigation in this field may result in the discovery of novel diagnostic and prognostic biomarkers for esophageal cancer, which could improve patient outcomes by enabling earlier detection and more focused treatment (24). The potential benefits of these treatments for patients make this an attractive area of research that calls for additional inquiry, despite the difficulties in establishing effective lncRNAbased therapeutics for esophageal cancer (29).…”
Section: The Role Of Lncrnas In Ec Pathogenesismentioning
confidence: 99%
“… 33 DEX regulates circular RNAs, thereby affecting the circ -0003340/miR-198/HMGA2 35 and circ0008035/miR-302a/E2F7 axes. 38 Moreover DEX reduces the expression of the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), thus reducing cellular viability in vitro and decreasing tumor growth in vivo 36 ( Figure 3 ). Taken together, these recent data argue that DEX could also mediate direct anti-tumor effects through a variety of mechanisms including epigenetic modifications, the induction of apoptotic and ferroptotic cell death, 42 a decrease in tumor cell migration via the expression of E-cadherin and the depletion of vimentin, and an arrest in cell cycle through the cessation of cyclin D1 synthesis.…”
Section: Introductionmentioning
confidence: 99%